Speech synthesis on the tracking surveillance device - Tran , Thu Ha; Pham , Minh Duong (Journal of Technical Education Science, 2016)
This paper presents the design and fabrication of the tracking surveillance device with speech synthesis algorithm by pairing method in which the users can monitor and manage their vehicles intuitively. At the same time, users can transmit the information to the driver to broadcast notifications. The speech by the unit selection-pairing synthetic method with words, phrases or sentences made speech after synthesis achieved high quality of natural level and easy listening level. The input text must be standardized into uppercase before processing the pairing synthesis with audio units by approriate context. Besides, the tracking surveillance device also has fully complicant features of QCVN 31:2014 BGTVT, the standard of the Ministry of Transport